2023
DOI: 10.1097/aog.0000000000005191
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in the Association of Endometriosis and Uterine Leiomyomas With the Risk of Ovarian Cancer

Abstract: Black and White participants with endometriosis had a higher risk of ovarian cancer; hysterectomy modified this association only among White participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…rs143094271-G has been associated with a decreased risk of having uterine fibroids (OR=0.70) 88 . Women with uterine fibroids have been found to be at increased risk of developing OC 89 . However, despite rs143094271-G being associated with women being less likely to have uterine fibroids, we found that rs143094271-G yielded an increased risk of developing HGSOC.…”
Section: Discussionmentioning
confidence: 99%
“…rs143094271-G has been associated with a decreased risk of having uterine fibroids (OR=0.70) 88 . Women with uterine fibroids have been found to be at increased risk of developing OC 89 . However, despite rs143094271-G being associated with women being less likely to have uterine fibroids, we found that rs143094271-G yielded an increased risk of developing HGSOC.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between hysterectomy and ovarian cancer is intricate. Previous studies suggest that hysterectomy may impede retrograde menstrual flow and the transfer of carcinogenic substances ( 60 ), thereby reducing the risk of ovarian cancer. Khoja et al.…”
Section: Eaoc Risk Factorsmentioning
confidence: 99%
“…58 Other studies found endometriosis and uterine fibroids, but not early menarche, to be relevant risks for Black patients with EOC. 59,60 Enriched data sets such as the Ovarian Cancer in Women of African Ancestry from diverse populations are critical to improve studies of disparities.…”
Section: Disparities In Risk Reduction and Prevention In Ovarian Cancermentioning
confidence: 99%
“…One such effort studied 10 EOC risk factors and found population risk attributably higher for Black women for all risk factors collectively including family history of breast cancer, body mass index, OCP use, aspirin, and body powder 58 . Other studies found endometriosis and uterine fibroids, but not early menarche, to be relevant risks for Black patients with EOC 59,60 . Enriched data sets such as the Ovarian Cancer in Women of African Ancestry from diverse populations are critical to improve studies of disparities.…”
Section: Ovarian Cancermentioning
confidence: 99%